2003
DOI: 10.1074/jbc.m301406200
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Tau Aggregation and Delayed Hippocampal Neuronal Death Induced by Persistent Thrombin Signaling

Abstract: Tau hyperphosphorylation, leading to self-aggregation, is widely held to underlie the neurofibrillary degeneration found in Alzheimer's disease (AD) and other tauopathies. However, it is unclear exactly what environmental factors may trigger this pathogenetic tau hyperphosphorylation. From several perspectives, the coagulation serine protease, thrombin, has been implicated in AD and activates several different protein kinase pathways but has not previously been shown how it may contribute to AD pathogenesis. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
70
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(72 citation statements)
references
References 104 publications
2
70
0
Order By: Relevance
“…Selected lines of HT22/dnGRK5GFP/M2, HT22/wtGRK5GFP/ M2, and HT22/GFP/M2 that express equivalent numbers of the transgene copies were used for this study. For all functional assays, the HT22 cells were differentiated, as previously described (19), before any treatments were applied.…”
Section: Materials-[methyl-mentioning
confidence: 99%
See 3 more Smart Citations
“…Selected lines of HT22/dnGRK5GFP/M2, HT22/wtGRK5GFP/ M2, and HT22/GFP/M2 that express equivalent numbers of the transgene copies were used for this study. For all functional assays, the HT22 cells were differentiated, as previously described (19), before any treatments were applied.…”
Section: Materials-[methyl-mentioning
confidence: 99%
“…HT22 cells seeded at a density of 5 ϫ 10 5 cells/well in six-well plates were allowed for differentiation, as previously described (19). The cells were then incubated with medium containing [methyl- (20).…”
Section: Materials-[methyl-mentioning
confidence: 99%
See 2 more Smart Citations
“…Through a variety of signal transduction mechanisms, PAR-1 has been shown to mediate effects of thrombin on astrocytic proliferation, process retraction, growth factor production, and also neuronal morphology and survival (11,12). PAR-1 has also been implicated in the pathogenesis of neuroinflammatory/degenerative disorders (13,14). Previous studies from our group demonstrated an important role for astrocytic PAR-1 up-regulation and activation in the neuropathogenesis of HIV-1 infection (15), characterized by neuroinflammation and neuronal injury.…”
mentioning
confidence: 99%